Ict Mediated Agricultural Extension : A Case Study - Sreenath Dixit,; G. Dileepkumar,; V. Balaji, (Journal of Agricultural Extension Management, 2025)
Recurrent droughts in the semi-arid parts of Andhra Pradesh affect the livelihoods of the poor and marginal farmers. Besides, recurrent droughts often cause large-scale water and food deficits, hunger, famine, exodus of people and animals, diseases, deaths, and many other severe, chronic socio-economic problems. Many of the rural communities appear to forget the miseries of one drought season with the onset of good rains; and those miseries usually continue from one drought to the next. This is due to the lack of awareness and nonavailability of the relevant information. There is an urgent need for a sustained information, communication, education and social mobilization among strategic sectors, especially the most vulnerable rural communities and their intermediaries, to improve the agriculture and to mitigate the effects of drought. Drought preparedness is preferable to relief, and information is the backbone of drought preparedness (UNSO, 2000))